Grassland management effect on ecosystem services in the livestock system in an oxisol from the Eastern high plains of Colombia - Rodríguez-Hernández, Nubia S.; Arango, Miguel; Moreno-Conn, Lina M.; Arguello, José Orlando; Bernal-Riobo, Jaime H.; Pérez-López, Otoniel (Frontiers in Environmental Science, 2023)
Colombia has a livestock population of approximately 28.2 million heads, of which 20.4% is found in the eastern high plains of the Orinoquia region. The extensive beef cattle system predominates, whose diet is based on native and introduced pastures of the genus Urochloa sp. which is deficiently managed, affecting productive and reproductive indexes due to the low adoption of technology. We evaluated potential sustainable intensive systems for cattle production, which contribute to maintaining the provision of environmental services. Between 2011 and 2015 in Agrosavia´s Research Center at Carimagua (4° 37'N and 71° 19' W) environmental and animal production variables were monitored in the following systems: a) degraded pastures recovered with tillage and fertilization, b) annual crop rotation with pastures, c) forest arrangements in strips and d) forest remnants in perimeter areas. Productive and reproductive variables were determined in animals such as weight gain, calving interval, among others while the pasture/crop productive variables included yield and forage quality. Regarding soil ecosystem services (ES) the macrofauna biodiversity and biogeochemical cycles were considered. Estimation of indicators was carried out through principal components analysis for soil physical, chemical and macrofauna variables to extract the two main components that explain the variance. For climate regulation of ES, measurement of soil organic carbon (SOC) storage at a depth of 20 cm and the annual accumulated greenhouse gas (GHG) emissions were included. Edaphic macrofauna biodiversity indicator value was sensitive to changes in management practices, with termites being the group with highest abundance. The indicator related to SOC was higher in the forest area compared to the crop-pasture rotation. The systems that involved lime amendments and fertilizers increased the value in the year of application. Indicators in the water regulation indicator value did not show significant differences among the options implemented during the years.